IMPLEMENTATION OF INFORMATION COMMUNICATION TECHNOLOGIES (ICTS) IN THE PROCESS OF TEACHING AND LEARNING IN PRIMARY SCHOOLS IN ZIMBABWE: THE SURVIVAL STAGE RAGES ON. - Ruparanganda, Fenton; Tafirenyika, Joice (IJRDO- Journal of Educational Research, 2017)
This study explored the state of preparedness of primary schools to use ICTs during the process of teaching and learning and the extent to which the primary schools are using ICTs in Zimbabwe. Quality education in the 21st century can be achieved if teachers infused ICTs in the teaching and learning process. A survey of ten primary schools in Manicaland province indicated that separate computer rooms have been set up where pupils from grade three to seven received basic computer appreciation lessons once a week at allocated times from a ‘specialist teacher’. Five teachers from each of the schools were interviewed, and ninety percent (90%) of them were not computer literate. Only ten percent (10%) of the teachers had acquired basic computer skills during teacher training and were all young teachers but did not use computers in their day-to-day teaching. Traditional pedagogic practices continued as the means of transmitting knowledge, skills and attitudes to pupils. The study also showed that although teachers were aware of the various learning opportunities to be realised by ICTs, and computers in particular, they lack the knowledge and skills on how to use ICTs to enhance quality learning. Most schools do not have the necessary ICT equipment and Internet connectivity is poor, non-existent or too expensive for most rural schools where the majority of the students learn. The study recommends that the use of computers as a tool in the teaching and learning process in the classroom can make learning student centred and the teacher assumes a new role of becoming a facilitator.